Endovascular therapy of acute ischemic stroke: report of the Standards of Practice Committee of the Society of NeuroInterventional Surgery. (24th January 2012) - Blackham, K A; Meyers, P M; Abruzzo, T A; Alberquerque, F C; Fiorella, D; Fraser, J; Frei, D; Gandhi, C D; Heck, D V; Hirsch, J A; Hsu, D P; Jayaraman, M; et al.
Abstract : Objective: To summarize and classify the evidence for the use of endovascular techniques in the treatment of patients with acute ischemic stroke. Methods: Recommendations previously published by the American Heart Association (AHA) (Guidelines for the early management of adults with ischemic stroke ( Circulation 2007) and Scientific statement indications for the performance of intracranial endovascular neurointerventional procedures ( Circulation 2009)) were vetted and used as a foundation for the current process. Building on this foundation, a critical review of the literature was performed to evaluate evidence supporting the endovascular treatment of acute ischemic stroke. The assessment was based on guidelines for evidence based medicine proposed by the Stroke Council of the AHA and the University of Oxford, Centre for Evidence Based Medicine (CEBM). Procedural safety, technical efficacy and impact on patient outcomes were specifically examined.